GIS-material for the archaeological project: Södra Änggård - Swedish National Heritage Board, UV Öst (Uppsala University, 2024)
The information in the abstract is translated from the archaeological report:
The Swedish National Heritage Board's Contract Archaeology Service, UV Öst, carried out a field evaluation in August 2002, and a final excavation in November the same year. The surveys covered remains of an Iron Age settlement by Stora Ängård, Lambohov, Slaka parish in Linköping municipality, Östergötland County, and were brought about by the municipality's plans of constructing a residential area with single-family houses on the location. The area is rich in ancient monuments and archaeological remains and the excavation was carried out nearby graves, stone fences and abandoned fields. The remains found were post holes, hearths, pits, pit systems and finds such as pottery, burnt clay, burnt bones and quartz. The investigations have shown that the site goes back to the Early Roman Iron Age and the Migration Period.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the field evaluation was to form an opinion of the type, intensity and extension of the archaeological remains found during the preceding survey, and date them if possible. The purpose of the final excavation was to document, date and interpret the features and structures. The result of the investigations will be seen in an Early Iron Age perspective, with a starting point in the known archaeological remains and previous surveys carried out in the area.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst utförde under augusti 2002 en arkeologisk förundersökning, samt under november samma år en arkeologisk slutundersökning. Undersökningarna omfattade rester av en järnåldersboplats och ägde rum vid Södra Änggård, Lambohov, Slaka socken, Linköpings kommun, Östergötland. Undersökningarna föranleddes av planerad småhusbebyggelse av Linköpings kommun. Området är rikt på fornlämningar och undersökningarna utfördes i nära anslutning till lämningar som gravar, stensträngar och fossil åkermark.Påträffade anläggningar bestod av stolphål, härdar, gropar, gropsystem samt ett antal fynd i form av keramik, bränd lera, brända ben och kvarts. Resultatet av undersökningarna har visat på att boplatsen härrör i tidig romersk järnålder och övergången till folkvandringstid.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att bedöma art, intensitet och utbredning av fornlämningarna i anslutning till de lämningar som upptäcktes vid utredning, samt att om möjligt datera dessa. Syftet med slutundersökningen var att dokumentera, datera och tolka anläggningar och de olika strukturerna inom fornlämningen. Resultaten av undersökningarna skall i första hand sättas in i ett äldre järnåldersperspektiv med utgångspunkt från den omgivande fornlämningsmiljön samt utifrån resultaten från tidigare utförda arkeologiska undersökningar i trakten.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Södra Änggård
Keywords: Roman Iron Age; romersk järnålder; Migration Period; folkvandringstid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive